Research on fiber-solid hybrid picosecond laser technology based on serrated aperture beam shaping - Li, Shun; Yang, Yang; Wang, Haiqiang; Zhu, Yunchen; Wang, Meijiao; Ma, Chao; Fan, Xinmin; Zhao, Yang; Jing, Huizhe; Liu, Daiping (Frontiers in Physics, 2025)
The high beam fill factor of the flat-top laser can effectively increase the output power of the laser without damaging the components. A fiber-solid hybrid high-energy picosecond pulsed laser system was studied, which realized the gain bandwidth matching between the fiber laser and the solid-state regeneration amplifier. In order to achieve the effective amplification of laser energy, the laser beam expander system and the serrated aperture were used to realize the conversion of Gaussian beam to flat-top beam, and a single-pass amplifier was used to generate a picosecond pulse laser output with a single pulse energy of 2.94 mJ. The front-end of the laser system is a Gaussian picosecond all-polarization-maintaining-fiber laser with an average output power of 400 mW, which is injected into the concave-convex cavity regeneration amplifier for power amplification, and the picosecond pulse laser output with a single pulse energy of 1.73 mJ and a repetition rate of 1 kHz is obtained when the pump current is 50 A. Then, using the laser beam expander system and the serrated aperture, a laser pulse with a flat-top beam energy distribution of 0.9 mJ was obtained, which can maintain a high fill factor within a transmission distance of 200 mm. Finally, a 4 mm diameter Nd:YAG gain module was used for single-pass power amplification to achieve a high-energy picosecond pulse laser output of 2.94 mJ, which has a broad application prospect in the field of laser manufacturing.